Online communication of citizen pressure groups in the face of the phenomenon of touristification in Spain - Francisco Javier Godoy-Martín (Frontiers in Political Science)
Spain is a proven tourist power, with a sector that contributes a high figure to the country’s economy. However, in recent years, tourist activity, especially in large cities, has encountered opposition from neighborhood groups that fight for a decrease in tourism, in order to preserve the identity of their neighborhoods and their living conditions. This research aims to describe the communication strategies employed by these citizen pressure groups on the social network X. For this purpose, an exploratory study was conducted using a quantitative methodology, whose main technique was content analysis, which was applied to a sample of 1,160 publications of 15 entities from different Spanish provinces. The results show that the main topics covered are related to the demonstrations and protest actions of these groups, as well as the tourism policies developed by authorities and the work meetings among different groups. Mobilization appears as a main objective, since 38.8% of the publications presented a tone of protest or denunciation. However, the findings also suggest that the social network X may be more suited to indirect lobbying actions.